Sequencing technology status of BRCA1/2 testing in Latin American Countries (2020)
The goal of this study was to survey laboratories in Latin America performing BRCA1 and BRCA2 (BRCA1/2) testing using the same questionnaire administered previously to other testing laboratories around the world1 . The initial study only captured information from two laboratories in the Latin American region. As this region of the world was under-represented, this study aimed to fill in the knowledge gap. A letter of invitation was sent to 12 laboratories directors of known academic centers in the region performing genetic testing. Two additional laboratories were identified, one at the XVII Congress of the Latin American Association of Genetics (ALAG) meeting in Mendoza, Argentina and a second at the 2019 American Society of Human Genetics meeting in Houston, TX, USA.